The Experience of Home Care Providers and Beneficiaries With Enhanced Training Requirements in Washington State. (December 2019) - Ordway, Anne; Johnson, Kurt L.; Kneale, Laura; Amtmann, Dagmar; Demiris, George
Objective: Our objective was to understand the perceived impact of Washington State's upgraded training and certification requirements of long-term care workers providing personal care services from the perspectives of consumers and home care aides.Methods: We applied conventional qualitative content analysis to semi-structured interviews with 17 consumers and 10 certified home care aides.Results: We found that consumers in this study put a high premium on directing many aspects of their personal care services. We also found that while home care aides supported what consumers desired for their own care, some were unsure how to reconcile providing individualized services with the State's standardized, competency-based training and certification program.Discussion: State-based efforts, such as the one in Washington State, serve as an important starting point for building a broader effort toward the identification of competencies and associated training standards for the home care workforce.